Psychopathology and borderline personality pathology associated with lifetime self-injurious behavior in adolescent psychiatric onpatients and detainees - Koenig, Julian; Brunner, Romuald; Schmidt, Johannes Michael; Parzer, Peter; Resch, Franz; Kaess, Michael (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2017)
Abstract: Objective: Self-injurious behavior (SIB) is a widespread phenomenon among adolescent psychiatric inpatients. It is also reported among delinquent adolescents detained in correctional facilities. While previous studies have addressed different functions of SIB within offender populations, here we investigate particular patterns of borderline personality pathology and psychopathology underlying SIB in both adolescent psychiatric inpatients and detainees. Method: Adolescent psychiatric inpatients and detainees were recruited consecutively. Participants completed self-reports on SIB, suicidal thoughts and behavior, borderline personality pathology, and general psychopathology. Predictors of lifetime SIB by group were analyzed. Results: Psychiatric inpatients (n = 77) and detainees (n = 50) did not differ with respect to lifetime SIB (57.14 % versus 54.00 %), whereas SIB within the past year did (67.53 % versus 14 %; χ2(1) = 6.158, p = .013). Psychiatric inpatients reported greater emotional problems (t(125) = 5.109, p < .0001) and greater borderline personality pathology. Those with lifetime SIB were characterized by greater emotional problems and borderline personality pathology, independent of their group. Results from regression analyses suggest no group-specific predictors of lifetime SIB. Conclusions: Although psychiatric inpatients endorse greater psychopathological distress, lifetime SIB among adolescent psychiatric inpatients and detainees is associated with similar patterns of psychopathology and borderline personality pathology.